The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/rs14133227
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Ability to Identify New Constructions in Urban Areas Using Images from Unmanned Aerial Vehicles, Google Earth, and Sentinel-2

Abstract: One of the main problems in developing countries is unplanned urban growth and land use change. Timely identification of new constructions can be a good solution to mitigate some environmental and social problems. This study examined the possibility of identifying new constructions in urban areas using images from unmanned aerial vehicles (UAV), Google Earth and Sentinel-2. The accuracy of the land cover map obtained using these images was investigated using pixel-based processing methods (maximum likelihood, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…The object-oriented methods used in this research, from the most to the least accurate, include SVM, RF, KNN, and Bayes. Therefore, the SVM method was used to classify aerial images in this research [21]. In the present study, the DSM image and NDVI were used to increase the accuracy of aerial image classification.…”
Section: Comparison Of Object-oriented Classification Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The object-oriented methods used in this research, from the most to the least accurate, include SVM, RF, KNN, and Bayes. Therefore, the SVM method was used to classify aerial images in this research [21]. In the present study, the DSM image and NDVI were used to increase the accuracy of aerial image classification.…”
Section: Comparison Of Object-oriented Classification Methodsmentioning
confidence: 99%
“…In this way, it is possible to effectively identify new constructions with the lowest cost and time for image processing. The full description of this method is provided in the study by Aliabad et al [21].…”
Section: Identification Of New Construction In Garden Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…(Sitanggang, 2023) which stated that the KNN method is more accurate than the SVM method in the classi cation. Arabi Aliabad et al (2022) consider KNN and SVM among object-oriented classi cation methods more accurate than others. Phiri et al (2020) used the results of 25 studies in classifying Sentinel-2 images and reported that the SVM and Bayes method has better accuracy for classi cation purposes.…”
Section: Introductionmentioning
confidence: 99%